032 Neurological sequelae of immune checkpoint inhibitors: a case series. Issue 6 (24th May 2018) - Silsby, Matthew; Duma, Stephen R; Mahant, Neil; Vucic, Steve; Henderson, Andrew
Abstract : Introduction: Monoclonal antibodies directed against co-stimulatory molecules on T cells (checkpoint inhibitors, CIs) are used to treat solid organ malignancies. Neurological complications are an increasingly recognised consequence of their use. We present three patients referred to the Neurology service at Westmead Hospital in 2017 with new neurological complaints following CI therapy. Cases: Patient 1, a 54 year old woman with stage IV non-small cell lung cancer treated with pembrolizumab (anti-PD-1), presented with cerebral vasculitis causing bilateral ACA territory cerebral infarction. Patient 2, a 59 year old woman with metastatic melanoma treated with ipilimumab (anti-CTLA4) and nivolumab (anti-PD-1), presented with ataxia, diplopia and ptosis consistent with Miller Fisher syndrome. Patient 3, a 77 year old woman with metastatic colorectal adenocarcinoma treated with nivolumab (anti-PD-1), presented with ocular myasthenia manifesting as fatigable ptosis and complex ophthalmoplegia. The diagnoses were made by clinical assessment with imaging and neurophysiological investigations where possible. Antibodies relevant to the neurological condition were negative, in keeping with previous reports. CIs were discontinued in all patients. Treatment included intravenous pulsed methylprednisolone followed by high dose oral taper in all patients. Additionally, Patient 1 was treated with infliximab and rituximab; Patients 2 and 3 received intravenous immunoglobulin followed by monthly maintenance therapy; Patient 2 underwent plasma exchange. Patients 1 and 2 recovered independent ambulation. Patient 3 died two months after presentation due to underlying malignancy. Conclusion: Checkpoint inhibitors block co-stimulatory molecules on T-cells, allowing the immune system to mount an anti-tumour response. The resulting immune dysregulation can also lead to organ-specific inflammatory and immune complications, of which neurological sequelae are increasingly recognised. The three reported patients highlight the spectrum of disease that can arise. Their occurrence within one year suggests an increasing incidence, and a need for increased vigilance. Early recognition is paramount as treatment with high dose corticosteroids, even in conditions that would not normally respond, is recommended.